Figurative Language Analysis in Poems of Maya Angelou - Br. Siburian, Andini Elisabeth; Herman; Neni Purba, Christian; Togi Hutahaean, David (Global Science Independent Journal, 2020)
In this research, the problems are arisen about what types of figurative language are used in Maya Angelou’s selected poems and what is thedominant of figurative language used in Maya Angelou’s poems. The objectives of this research to find out the types of figurative language that are used in Maya Angelou’s selected poems and to find out the dominant of figurative language used in Maya Angelou’s poems. The methodology, which used in this research, is the qualitative research. The subject of the current study is an analysis of figurative language in poems of Maya Angelou entitled “Still I Rise” (1978), “On the Pulse of Morning” (1993), “Phenomenal Woman” (1995), “Caged Bird” (1969), and “A Brave and Startling Truth” (1995). The data were collected from the book entitled “The complete collected poems of Maya Angelou” published by Random House, United States of American in 1994. After investigating the types of figurative language in the five mentionedMaya Angelou’s poems, the researchers found the total 69 sentences that contain examples of figurative language. Metaphor consists of 24 sentences with percentage 34,8%; personification consist of 21 sentences with percentage 30,4%; hyperbole 12 consist of sentences with percentage 17,4%; simile consist of 9 sentences with percentage 13%; irony consist of 2 sentences with percentage 2,9%; and metonymy consist of one sentence with percentage 1,4%. It can be indicated that the dominant type of figurative language used in Maya Angelou’s poems is metaphor.